Обработка семян пшеницы сорта "Навруз" гуминовым препаратом - Солихова, Махина Имомалиевна (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25–28 апреля 2023 г.)
One of the urgent tasks of Agro-chemistry is the establishment of the effect of quantitative indicators of fertilizer in agriculture. The solution to such problems have been determined by the experimental part of the work, which is created because of the appearance of new research methods and equipping with modern apparatus and equipment of agrochemical laboratories. Humic substances increase the intensity of photosynthesis and respiration, increase protein and phosphorus metabolism in plants. Practice shows significant progress in establishing a more accurate balance of nitrogenous fertilizers in the plant soil system, as well as in the knowledge of the intensity of the transformation of nitrogenous fertilizers in the soil and plants. It is established, that the treatment of the seeds of agricultural crops with certain doses in the plants, showed earlier emergence of seedlings and in the field conditions of ripening fruit and increase yield. The main purpose of this research was to find out the effect of humic acids on germination energy and total germination, growth and development of wheat seeds. During the experiments, the seeds were treated with humic peat fertilizer with different concentrations of 0,001%, 0,002%, 0,003%. These studies in laboratory conditions with wheat confirmed this position.